System performance analysis of hybrid time-power switching protocol of EH bidirectional relaying network in amplify-and-forward mode - Phu Tran Tin; Minh Tran; Tan N. Nguyen; Thanh-Long Nguyen (Institute of Advanced Engineering and Science, 2019)
In this paper, we investigate system performance in term of throughput and ergodic capacity of the hybrid time-power switching protocol of energy harvesting bidirectional relaying network. In the first stage, the analytical expression of the system throughput and ergodic capacity of the model system is proposed and derived. In this analysis, both delay-limited and delay-tolerant transmission modes are presented and considered. After that, the effect of various system parameters on the proposed system is investigated and demonstrated by Monte-Carlo simulation. Finally, the results show that the analytical mathematical and simulated results match for all possible parameter values for both schemes.